Integrating sport science with high performance sport programme in Singapore - Lim, F. C. L. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
The Singapore Sports Institute (SSI) has shifted from a service-centric to a programme-centric athlete support model that is evidence-based. In the service-centric model, the type and profile of services and interventions delivered to the athlete is determined primarily by the demands from the athlete and his/her Coach. In the programme-centric model, the type of services and interventions delivered to the athlete are determined by the needs and objectives of the sport programme and each member of the support team is given the professional space to provide inputs based on their expertise with the periodization programme as the centre of focus. Evidence-based practice refers to the use of objective data to determine the course of action and to measure the effectiveness of interventions delivered to the athlete. Such an approach does not only require the Sport Scientists to use published data to design their programmes or intervention plans, but also require the Sport Scientists to objectively measure the effectiveness of their interventions using data derived from measurement of relevant outcome variables that are sport-specific. Since mid-2012, SSI has been experimenting with the programme-centric support model and evidence-based practise on the Singapore`s Waterpolo Team and will be expanding this model of athlete support to other sports. SSI will be constructing a Sport Simulation Laboratory and an Environmental Simulation Laboratory at the Singapore Sports Hub to better support ourathletes. The Sport Simulation Laboratory comprises "domes" which can play video feeds of sport scenes which the Sport Psychologist can use to enhance mental skill training such as focus, concentration, attention, relaxation and stress management, and behaviour modification. The Environmental Simulation Laboratory allows the simulation of climatic and altitude conditions and the use of heat acclimation (HA) to enhance sport performance. The thermoregulatory, cardiovascular and metabolic adaptations derived from HA overlaps with altitude training, but HA has better consistency in inter-individual responses compared with altitude training. The introduction of these technologies will provide Sport Scientists with more tools and options to support Team Singapore athletes using the programme-centric and evidence-based models.